Dynamic and Tunable Threshold Voltage in Organic Electrochemical Transistors. Issue 15 (2nd March 2018) - Doris, Sean E.; Pierre, Adrien; Street, Robert A.
Abstract: In recent years, organic electrochemical transistors (OECTs) have found applications in chemical and biological sensing and interfacing, neuromorphic computing, digital logic, and printed electronics. However, the incorporation of OECTs in practical electronic circuits is limited by the relative lack of control over their threshold voltage, which is important for controlling the power consumption and noise margin in complementary and unipolar circuits. Here, the threshold voltage of OECTs is precisely tuned over a range of more than 1 V by chemically controlling the electrochemical potential at the gate electrode. This threshold voltage tunability is exploited to prepare inverters and amplifiers with improved noise margin and gain, respectively. By coupling the gate electrode with an electrochemical oscillator, single‐transistor oscillators based on OECTs with dynamic time‐varying threshold voltages are prepared. This work highlights the importance of electrochemistry at the gate electrode in determining the electrical properties of OECTs, and opens a path toward the system‐level design of low‐power OECT‐based electronics. Abstract : The threshold voltage of organic electrochemical transistors (OECTs) can be tuned precisely over a range of more than 1 V by chemically controlling the electrochemical potential at the gate electrode. By using chemical systems with time‐dependent electrochemical potentials, single‐transistor oscillators with dynamic threshold voltage are implemented. The control afforded by this strategy dramatically simplifies the implementation of OECT‐based circuits.